Performance of the COPD Assessment Test in patients with connective tissue disease-associated interstitial lung disease. (April 2019) - Suzuki, Atsushi; Kondoh, Yasuhiro; Swigris, Jeffrey James; Matsuda, Toshiaki; Kimura, Tomoki; Kataoka, Kensuke; Ando, Masahiko; Hashimoto, Naozumi; Sakamoto, Koji; Hasegawa, Yoshinori
Abstract: Background: Patients with connective tissue disease-associated interstitial lung disease (CTD-ILD) often experience impaired health status. In daily clinical practice, a short and easy instrument for assessing health status would be useful to help better understand the patient's condition. The COPD Assessment Test (CAT) is a simple questionnaire about respiratory symptoms and their impact. We aimed to examine the CAT's performance characteristics and to generate data to support its reliability and validity in patients with CTD-ILD. Methods: We used data from 132 CTD-ILD patients evaluated at Tosei General Hospital from July 2011 to July 2016 to assess the cross-sectional and longitudinal validity of the CAT. Results: The mean age of the patients was 64.5 years and 87 (66%) were women. There were no significant differences in CAT score between any of the CTD subgroups. Internal consistency (Cronbach's α = 0.881) and repeatability (intraclass correlation coefficient [ICC] = 0.803) for the CAT score were acceptable. At baseline, CAT score was significantly associated with clinically meaningful measures of physiologic function, exercise capacity, and dyspnea. Change in CAT score over 6–12 months was also associated with change in other measures. In the distribution- and anchor-based analyses, the estimated minimal clinically important difference of CAT score was 1–4 points. Conclusion: These data support the validity and reliability of CAT as a sensitive measure for assessing health status in patients with CTD-ILD. Highlights: The CAT score possessed adequate internal consistency (Cronbach's α = 0.881) and repeatability (ICC = 0.803) in patients with CTD-ILD. In cross-sectional analyses, the CAT score significantly correlated with clinically relevant anchors in patients with CTD-ILD. In longitudinal analyses, CAT scores were responsive to changes in disease status over time in patients with CTD-ILD.